2020
DOI: 10.1186/s12957-020-01880-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metastatic lymph nodes in cN0 thoracic esophageal cancer patients with inconsistent pathological lymph node diagnosis

Abstract: Background Preoperative clinical diagnosis of lymph node (LN) metastasis and subsequent pathological diagnosis are often not in agreement. Detection of false-negative LNs is essential in selecting an optimal treatment strategy, and most importantly, the presence of false-negative LN is itself a significant prognostic indicator. Therefore, at present, there is an urgent need to establish more accurate and individualized evaluation methods for LN metastasis. Methods Of 213 cN0 patients who underwent curative es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…However, the accuracy of CT is unsatisfactory when LNs greater than 10-mm diameter are considered positive for metastasis [ 33 , 34 ]. Wakita et al [ 35 ] found that among the 213 patients who were diagnosed as cN0 by CT and underwent curative esophagectomy without preoperative neoadjuvant treatment, 60 (28%) patients had LN metastasis diagnosed pathologically. An important limitation was that metastatic lymph nodes might present without an apparent enlargement in size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the accuracy of CT is unsatisfactory when LNs greater than 10-mm diameter are considered positive for metastasis [ 33 , 34 ]. Wakita et al [ 35 ] found that among the 213 patients who were diagnosed as cN0 by CT and underwent curative esophagectomy without preoperative neoadjuvant treatment, 60 (28%) patients had LN metastasis diagnosed pathologically. An important limitation was that metastatic lymph nodes might present without an apparent enlargement in size.…”
Section: Discussionmentioning
confidence: 99%
“…Even with PET/CT, a large number of small metastatic lesions can be difficult to detect [ 33 , 38 , 39 ]. A previous study has reported that lowering the size criteria and combining the axial ratio (short-axis diameter/long-axis diameter) would increase sensitivity [ 16 , 35 , 40 ]. Therefore, in the present study, LNs were diagnosed as suspected metastatic nodes in the absence of pathological confirmation, when the short-axis diameter exceeding 5 mm and the shape of the node was round (axial ratio exceeding 0.66).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there might be some errors in the nodal mapping. Furthermore, the optimal imaging diagnostic criteria of LNR remain controversial (22)(23)(24). More studies with large sample sizes in different centers are needed to verify our results.…”
Section: Discussionmentioning
confidence: 74%
“…Even with PET/CT, a large number of small metastatic lesions can be di cult to detect [34,38,39]. A previous study has reported that lowering the size criteria and combining the axial ratio (short-axis diameter/long-axis diameter) would increase sensitivity [16,40,41]. Therefore, in the present study, LNs were diagnosed as suspected metastatic nodes in the absence of pathological con rmation, when the short-axis diameter exceeding 5 mm and the shape of the node was round (axial ratio exceeding 0.66).…”
Section: Discussionmentioning
confidence: 99%